Analisa Keandalan Instrumentasi Pada Lime Kiln Unit Menggunakan Metode Reliability Centered Maintenance (RCM) di PT. Indah Kiat Pulp and Paper Perawang - Andriyan, Septa; Jufrizel, Jufrizel; Ulah, Aulia; Faizal, Ahmad (Universitas Al Azhar Indonesia, 2024)
PT. Indah Kiat Pulp and Paper Perawang is a company that prioritizes paper production. There is a crucial unit known as the lime kiln within the company. Issues occurring within this unit often disrupt the overall production process. Therefore, conducting reliability analysis on the instrumentation of this unit is highly important. This research utilizes the Reliability Centered Maintenance (RCM) method. The objective of this study is to determine which devices within the lime kiln are most vulnerable to problems by calculating the Risk Priority Number (RPN) for each component, evaluating the reliability level of these devices, and providing optimal maintenance schedule recommendations. The research findings indicate the sequence of RPN values for lime kiln instrumentation from highest to lowest as follows: temperature sensor 336, on-off valve 288, flow transmitter 252, control valve 245, proximity sensor 240, pressure gauge 216, sensor indication of motorized damper 210. Furthermore, the reliability values of each instrumentation did not meet the threshold set by the Indonesian Industry Standard (SII), which is 0.7. Therefore, it can be concluded that maintenance action is required for these instrumentation devices. Maintenance schedule recommendations for temperature sensor are 252 days, on-off valve 294 days, flow transmitter 293 days, control valve 251 days, proximity sensor 293 days, pressure gauge 352 days, and sensor indication of motorized damper 353 days.Keywords – Keandalan, Instrumentasi, Maintenance, Lime kiln, RCM.